Distribution of Woody Plant Species Among Different Disturbance Regimes of Forests in a Temperate Deciduous Broad-Leaved Forest - Xi, Jingjing; Shao, Yizhen; Li, Zihao; Zhao, Pengfei; Ye, Yongzhong; Li, Wang; Chen, Yun; Yuan, Zhiliang (Frontiers in Plant Science, 2021)
Forests in different disturbance regimes provide diverse microhabitats for species growth. However, whether the species distribution of wood plant is random or follows ecological specialization among forests in different disturbance regimes remains to be elucidated. In this study, four 1 hm2 (100 m × 100 m) forest dynamic monitoring plots in different disturbance regimes of forests were randomly selected in a temperate deciduous broad-leaved forest. We examined the specificity of woody plants to forests through network analysis. Torus-translation test was used to analyze the species distribution preference of woody plants to forests in different disturbance regimes. The specialization index of woody plants was 0.3126, and that of shrubs (51.01%) was higher than that of trees (25.16%). Moreover, 66.67% (38/57) of woody plants were associated with different forests. More shrub species (70.00%) had specific preferences than tree species (45.95%) with respect to forests in different disturbance regimes. Our findings suggest that the distribution of woody plants among forests with different disturbance regimes is not random but is specialized. Different woody plants show different community preferences in different disturbance regimes of forests. Shrubs show higher specialization than trees in different disturbance regimes of forests.